The Role of the Lateral Habenula in Suicide: A Call for Further Exploration - Marks, Rocky B.; Wee, Janelle Y.; Jacobson, Samantha V.; Hashimoto, Kimi; O’Connell, Katherine L.; Golden, Sam Adler; Baker, Phillip Michael; Law, Keyne Catherine (Frontiers in Behavioral Neuroscience, 2022)
Despite decades of significant effort in research, policy, and prevention, suicide rates have continued to rise to the current peak of 14.6 per 100,000 deaths (CDC, 2020). This has resulted in a concerted effort to identify biomarkers associated with suicidal behavior in the brain (Calati et al., 2020; Sudol & Mann, 2017), to provide predictions that are better than chance at discerning who will die by suicide (Franklin et al., 2017). We propose that the lateral habenula (LHb), and its dysfunction during suicidal crisis, is a critical component of the transition from suicidal ideations to self-harm. Moreover, the LHb - a key functional node in brain reward circuitry - has not been ascribed a contributory role in suicidal behavior. We argue that the LHb anchors a “suicide circuit” and call for suicide researchers to directly examine the role of the LHb, and its long-term modulation, in response to negative affect in suicidal behavior. Discerning the neural mechanisms of this contribution will require the collaboration of neuroscientists and psychologists. Consequently, we highlight and discuss research on LHb as it relates to suicidal ideation, suicidal behavior, or death by suicide. In so doing we hope to address the bench-to-bedside translational issues currently involved in suicide research and suggest a developmental framework that focuses on specific structures motivated by theoretical anchors as a way to incorporate neurobiological findings within the context of clinical theory.